Perceptions of positive and negative clinician communication in obstetrical visits from the perspectives of pregnant patients who use substances - Abisola Olaniyan; Mary Hawk; Dara D. Mendez; Steven M. Albert; Natalie Stern; Sneha Patnaik; Judy C. Chang (PEC Innovation)
Objectives: To explore the perceptions of pregnant patients who use substances regarding positive or negative clinician communication during obstetrical care. Methods: We analyzed qualitative data from 85 semi-structured interviews with pregnant patients who reported or tested positive for substance use, which explored their interaction with obstetric providers during their first prenatal visit. This analysis focuses on patients' perceptions of negative versus positive clinician communication behaviors. Results: Eighty-five participants described clinician communication behaviors they felt affected their feelings about the clinician and their willingness to talk about prenatal substance use and other sensitive topics. Negative behaviors included clinicians (1) expressing judgment, (2) rushing through the consultation and providing limited information to patients, and (3) using statements or behaviors that made patients feel dehumanized. Positive behaviors included clinicians (1) explicitly expressing care for the patient, (2) creating rapport by soliciting patient stories and building relationships, and (3) demonstrating attentive listening. Innovation: To our knowledge, our study is the first to explore clinician communication behavior with a focus on prenatal substance use from the perspective of pregnant people using substances. Conclusion: Our findings highlight pregnant patients' perspectives on communication patterns that could improve patient-clinician interactions and, in turn, maternal health care and outcomes.